Vocational Education and Training's Effect on Employment Opportunities in Northwestern Vietnam's Ethnic Minority Regions - Nguyen, Nui Dang (Journal of Ecohumanism, 2024)
This study examines how vocational education and training impact employment prospects for ethnic minority workers in the Northwest area of Vietnam, specifically looking at opportunities for paid employment and the shift from agriculture to other industries. Through logistic regression analysis, it was determined that vocational training greatly improves employment opportunities, with age and technical skills being key factors in securing a job. Individuals with vocational training experience enhanced job prospects compared to individuals lacking such training or holding advanced academic qualifications. The study emphasizes a significant shift of skilled workers from agriculture to other industries due to improved career prospects and higher earnings. The report also highlights fluctuations in employment likelihoods according to gender, geographic area, and sector throughout time. The study suggests that combining vocational training with local socio-economic development, focusing on vocational coaching, and establishing partnerships for training can greatly enhance job opportunities for ethnic minority workers in Vietnam. The government should create vocational training programs tailored to local socio-economic development needs and assist businesses in educating and hiring individuals from varied ethnic backgrounds to boost economic growth and decrease employment inequalities.